Pengaruh Sejarah Situs Bongal Desa Jago-jago terhadap Penyebaran Islam di Sumatera Utara - Shaleha, Puspa Unsya; Sumantri, Pulung; Nababan, Surya Aymanda (Medan Resource Center, 2025)
This study aims to analyze the relationship between the Bongal Site and the historical traces of Islamic civilization in North Sumatra, as well as to examine the impact of Islam’s arrival on the identity and daily life of local communities based on archaeological findings at the Bongal Site. The research employs a qualitative approach with historical analysis, incorporating document studies, artifact examination, and other supporting evidence. The findings indicate that the introduction of Islam to North Sumatra, as evidenced by discoveries at the Bongal Site in Jago-jago Village, dates back to the 7th–8th century CE. This site is a significant archaeological landmark in Sumatra, providing early proof of Islam’s presence in the Indonesian archipelago. As of 2023, the Fansuri Bongal Museum has collected 207 artifacts, comprising 4,062 human-related artifacts and 2,861 additional objects. These findings are categorized into ten major groups: beads, Islamic medical instruments, Middle Eastern glassware, Chinese and West Asian ceramics, coins (Islamic, Indian, and Chinese), metals and their processing technology, the textile and food industries, palm fiber and ship fragments, aromatic resins and spice wood, and finally, nibung wood fragments.